2019
DOI: 10.1002/anie.201900692
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Adaptive Dynamic Metal‐Organic Soft Hybrid for Imaging and Biological Delivery

Abstract: As olvent responsive dynamic nanoscale metalorganic framework (NMOF) [Zn(1a)(H 2 O) 2 ]h as been devised based on the self-assembly of Zn II and asymmetric bola-amphiphilic oligo-(p-phenyleneethynylene) (OPE) dicarboxylate linker 1a having dodecyl and triethyleneglycolmonomethylether (TEG,p olar) side chains.I nT HF solvent, NMOF showed nanovesicular morphology (NMOF-1)w ith surface decorated dodecyl chains.I nw ater and methanol, NMOF exhibited inverse-nanovesicle (NMOF-2)a nd nanoscroll (NMOF-3)m orphology,r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This exclusive photoinduced reversible morphology transformation from spheres to bers could enable the use of such materials in the domains of photoactuators 4,39 and delivery media. 45,68 Next, a rheology study was performed for Eu-pcCPG-O and Eu-pcCPG-C, which showed the viscoelastic nature of both the photoisomers of pcCPG. Notably, G 0 for both Eu-pcCPG-O and Eu-pcCPG-C was found to be similar under less % strain, which decreases along with an increase in the % strain.…”
Section: Synthesis Characterization and Photochromism In Coordination Polymer Gelsmentioning
confidence: 99%
“…This exclusive photoinduced reversible morphology transformation from spheres to bers could enable the use of such materials in the domains of photoactuators 4,39 and delivery media. 45,68 Next, a rheology study was performed for Eu-pcCPG-O and Eu-pcCPG-C, which showed the viscoelastic nature of both the photoisomers of pcCPG. Notably, G 0 for both Eu-pcCPG-O and Eu-pcCPG-C was found to be similar under less % strain, which decreases along with an increase in the % strain.…”
Section: Synthesis Characterization and Photochromism In Coordination Polymer Gelsmentioning
confidence: 99%
“…The possibility of using OPE derivatives for dual imaging and drug-carrying systems represents a goal for many scientists. In 2019, Maji et al [ 28 ] developed a metal organic hybrid system for imaging and drug delivery that is based on functionalized OPEs possessing solvent-adaptive behavior. These oligomers form a nanoscale metal organic framework (NMOF) with different morphologies, depending on the solvent ( Figure 3 a).…”
Section: Optical Properties Of Opesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are documented as one of the most significant classes of porous materials due to their distinctive features and versatility . However, the development of water‐stable MOFs still remains a great challenge for applications, in terms of five major areas—adsorption and/or separation, sensing, catalysis, drug delivery, and proton conduction—where such applications are conducted in water‐containing environments .…”
Section: Introductionmentioning
confidence: 99%